2022
DOI: 10.1038/s42004-022-00649-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced preparation of fragment libraries enabled by oligonucleotide-modified 2′,3′-dideoxynucleotides

Abstract: The ever-growing demand for inexpensive, rapid, and accurate exploration of genomes calls for refinement of existing sequencing techniques. The development of next-generation sequencing (NGS) was a revolutionary milestone in genome analysis. While modified nucleotides already were inherent tools in sequencing and imaging, further modification of nucleotides enabled the expansion into even more diverse applications. Herein we describe the design and synthesis of oligonucleotide-tethered 2′,3′-dideoxynucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…An essential requirement for these compounds is the compatibility of the unnatural linker with DNA polymerases to enable the use of the attached oligonucleotide as a priming site. We optimized the structure of the linker and identified polymerases able to use OTDDNs as substrates, as well as polymerases able to perform read‐through [ 30 ]. These findings pave the way for straightforward DNA labelling by any desired oligonucleotide irrespective of the sequence context of the template.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential requirement for these compounds is the compatibility of the unnatural linker with DNA polymerases to enable the use of the attached oligonucleotide as a priming site. We optimized the structure of the linker and identified polymerases able to use OTDDNs as substrates, as well as polymerases able to perform read‐through [ 30 ]. These findings pave the way for straightforward DNA labelling by any desired oligonucleotide irrespective of the sequence context of the template.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have demonstrated the concept of semi‐targeted RNA sequencing and identified a plethora of TMPRSS2 3′‐terminal fusion partners in PCa. We have previously shown that the introduction of sequencing adapters via enzymatic incorporation of base‐modified dideoxynucleotides improves NGS library preparation [ 30 , 34 ]. This work further expands the applicability of OTDDNs and suggests a semi‐targeted sequencing technique for transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained base-modified conjugates with ≥97% purity and ≥20% yield. We optimized the structure of an unnatural linker and identified reverse transcriptases able to use OTDDNs as substrates as well as polymerases able to perform read-through [ 21 ]. This technology enables straightforward cDNA labelling with any desired synthetic oligonucleotide and easy addition of unique molecular labels.…”
Section: Resultsmentioning
confidence: 99%
“…The first generation of sequencing technology, which emerged in the early 2000s, included chemical analysis and enzymatic sequencing methods. These methods relied on chain termination using 2′,3′- dideoxynucleotides (ddNTPs) ( Medžiūnė et al, 2022 ). First-generation sequencers, such as the ABI Prism, were developed to automate the sequencing process and could analyze 4 to 96 samples per single run ( Kchouk et al, 2017 ).…”
Section: Beyond Genome Editingmentioning
confidence: 99%